Eclipse TEA Revealed Building Plug-ins and Creating Extensions for Eclipse - Duft, Markus (Apress, 2018)
Discover the open source Eclipse Tasking Engine Advanced (TEA) project in this compact to-the-point book. It covers how to automate tasks using TEA and focuses on simplifying and aiding the creation of extensions for the Eclipse IDE in a way which makes them accessible both from the IDE's UI and in a headless fashion from the command line. Additionally, Eclipse TEA Revealed explores the library of pre-built components included with TEA, mostly in the area of rich client platform (RCP)-based Java application development, for building projects, updating sites, dealing with target platforms, and more. After reading and using this book, you'll be up to speed on the fundamentals of Eclipse TEA and ready to use it for more productive Java-based application builds and developments. You will: View TEA's internal architecture Work with TEA's APIs Write TEA components Use the pre-built TEA components Set up headless environments using TEA.